68.4k views
1 vote
Find the general solution for the following homogeneous equations. PLEASE SHOW SOLUTIONS

1) (xy+y2)dx−x2dy=0 (hint: let u=y/x, so y=ux, dy=xdu+udx))

2) 2x2ydx=(3x3+y3)dy. (hint: let v=x/y, so x=vy, dx=vdy+ydv)

User Kornero
by
6.3k points

1 Answer

4 votes

Follow the hints.

1. Let
u=\frac yx, so that
y=ux and
\mathrm dy=x,\mathrm du+u\,\mathrm dx. Substituting into


(xy+y^2)\,\mathrm dx-x^2\,\mathrm dy=0

gives


(ux^2+u^2x^2)\,\mathrm dx-x^2(x\,\mathrm du+u\,\mathrm dx)=0


u^2x^2\,\mathrm dx-x^3\,\mathrm du=0

and the remaining ODE is separable:


x^3\,\mathrm du=u^2x^2\,\mathrm dx\implies(\mathrm du)/(u^2)=\frac{\mathrm dx}x

Integrate both sides to get


-\frac1u=\ln|x|+C


-\frac xy=\ln|x|+C


\boxed{y=\frac xCx-\ln}

2.
Let [tex]v=\frac xy, so that
x=vy and
\mathrm dx=v\,\mathrm dy+y\,\mathrm dv. Then


2x^2y\,\mathrm dx=(3x^3+y^3)\,\mathrm dy

becomes


2v^2y^3(v\,\mathrm dy+y\,\mathrm dv)=(3v^3y^3+y^3)\,\mathrm dy


2v^3y^3\,\mathrm dy+2v^2y^4\,\mathrm dv=(3v^3y^3+y^3)\,\mathrm dy


2v^2y^4\,\mathrm dv=(v^3y^3+y^3)\,\mathrm dy

which is separable as


(2v^2)/(v^3+1)\,\mathrm dv=\frac{\mathrm dy}y

Integrating both sides gives


\frac23\ln|v^3+1|=\ln|y|+C


\ln|v^3+1|=\frac32\ln|y|+C


v^3+1=Cy^(3/2)


v=\sqrt[3]{Cy^(3/2)-1}


\frac xy=\sqrt[3]{Cy^(3/2)-1}


\boxed{x=y\sqrt[3]{Cy^(3/2)-1}}

User Nev Stokes
by
5.8k points